Tangeretin improves hepatic steatosis and oxidative stress through the Nrf2 pathway in high fat diet-induced nonalcoholic fatty liver disease mice. Issue 5 (16th February 2022) - Ke, Zunli; Tan, Si; Li, Haiyang; Jiang, Shanshan; Li, Yuping; Chen, Rui; Li, Mingxia
Abstract : Tangeretin supplementation could improve the pathological features of NAFLD in obese mice induced by a high fat diet, and this beneficial function may be associated with the activation of the hepatic Nrf2 pathway. Abstract : Nonalcoholic liver disease (NAFLD) is a pathological condition characterized by excessive fat deposition in the liver, and NAFLD usually has a close relationship with obesity or metabolic syndrome. Currently, oxidative stress is considered as an important risk factor in the progression of NAFLD, therefore, effective amelioration of oxidative stress has emerged as a promising way to improve NAFLD. Tangeretin is a natural compound having various pharmacological activities including antioxidation and hepatoprotection. However, whether tangeretin is able to improve NAFLD through reducing hepatic oxidative stress is rarely reported. In our work, the preventive effects of tangeretin on a NAFLD mouse model induced by a high fat (HF) diet were studied. The results exhibited that tangeretin supplementation observably slowed down NAFLD progression through alleviation of metabolic indexes such as glucose tolerance, serum lipid levels and inflammatory factors, hepatic oxidative stress as well as steatosis. qRT-PCR showed that tangeretin supplementation increased the nuclear factor erythroid-2-related factor 2 ( Nrf2 ) expression and then upregulated the expression of its downstream factors including HO-1, GCLC, NQO1 and GSTA2 . Furthermore, the expression of the hepatic nucleus, Nrf2, HO-1 and GCLC, was also seen to be significantly enhanced in WB analysis. Taken together, this study implies that tangeretin might alleviate NAFLD through lowering oxidative stress in the liver by partial modulation of the Nrf2 pathway. Our study provided theoretical support that tangeretin could be used as a dietary therapy for obesity related-NAFLD or related metabolic syndrome.